Quo vadis coaching in Portugal? - Fontes, A.; Dello Russo, S. (10th Conference of the Iberoamerican Academy of Management (IAM), 2017)
Coaching practices are increasingly spread across the world and Portugal represents no exception, although in this country the coaching profession is more recent. Given the established effectiveness of this practice, notwithstanding a number of critiques particularly related to the difficulty of explaining its effectiveness as well as to its replicability, we aimed to better understand the coaching context in Portugal. A survey for coaching practitioners distributed online and a final sample of 187 coaches participated. Findings show that the majority of respondents adopt theoretical frameworks rooted in psychology or NLP and they tend to adopt also specific techniques/tools, particularly for diagnostic purposes. Although, the use of specific tools that would make the practice of coaching more “replicable” or “testable” is not commonly spread, especially in more advanced phases of coaching programs. Among the positive consequences of coaching, the coaches report most impact on self-awareness and hope/optimism, and less on leadership competencies, despite leadership being one the most demanded areas for working during coaching sessions. Interestingly, some negative consequences of coaching are also reported. We discuss these findings advocating for more scientific research on the mediating mechanisms that are responsible for its effectiveness as well as for theory-driven methodologies that can be replicated and standardized, contributing therefore to coaching effectiveness.